Passivation of lanthanide surface sites in sub-10 nm NaYF(4):Eu(3+) nanocrystals - Banski, M. (Springer Netherlands, 2012)
We examined in detail the optical properties of NaYF(4):Eu(3+) nanocrystals of ~9 nm in diameter. For such small nanocrystals roughly 17 % of Y(3+) ions occupy surface sites and can be efficiently substituted by optically active Eu(3+) ions. In order to determine the influence of surface Eu(3+) on the optical properties of the whole nanocrystal, small β-NaYF(4):Eu(3+) nanocrystals with homogenous size distribution were prepared using trioctylphosphine oxide as a coordinating solvent. In order to passivate the surface sites, a thin β-NaYF(4) shell was further deposited on nanocrystals core and the optical properties were investigated. For this purpose absorption, photoluminescence, photoluminescence excitation, and photoluminescence decays were recorded and analyzed. The optical characteristics of surface Eu(3+) significantly diminish for surface passivated nanocrystals. We calculated the increase of quantum yield to the value of 64 % when NaYF(4):Eu(3+) core was capped by undoped shell. The optical spectroscopy techniques were shown to be sufficient in determination of surface passivation of nanocrystals with high surface to volume ratio.